Direct conversion of carbon dioxide to liquid hydrocarbons over K-modified CoFeOx/zeolite multifunctional catalysts. (November 2022) - Qin, Keye; Men, Yong; Liu, Shuang; Wang, Jinguo; Li, Zhuping; Tian, Dandan; Shi, Tianle; An, Wei; Pan, Xiaoli; Li, Lin
Abstract: Direct conversion of carbon dioxide (CO2 ) to high added-value chemicals is available for reducing reliance on fossil fuels and mitigating CO2 emissions, but both the chemical inertness of CO2 and the difficulty of carbon chain growth make it difficult to enhance the activity of the catalyst. In this work, we developed a multifunctional catalyst composed of K-promoted spinel structured CoFeOx and HZSM-5 that efficiently converted CO2 to light-weight hydrocarbons via CO2 modified Fischer-Tropsch synthesis path (CO2 -FTS), and the best catalyst exhibited a remarkably efficient CO2 conversion of 51.2% and liquid hydrocarbons space-time yield (STY) of 3.4 μmolC5+ ·gcat −1 ·s −1 along with an extremely low selectivity of 5.5% toward undesired CO. By analysis of structural characterizations and reaction results, the noticeable performance of the multifunctional catalyst critically lies in the beneficial interaction between Co and Fe, the promoting effect of potassium, and the concertedly synergistic effect between K-CoFeOx and HZSM-5. In situ XRD, XPS, and TPD characterizations further indicate that the introduction of cobalt promotes the reduction of iron by forming a Fe 0 -rich FeCo alloy, which is beneficial for the adsorption of intermediate CO and facilitates the in situ generation of active iron carbide. K as an electronic promoter is added to increase the surface basicity, enhance the adsorption of CO2 and weaken the adsorption of H2, which favor CO2 conversion and carbon chain growth. Additionally, through passivation of the strong acidic site of HZSM-5 by Si treatment and varying the mixing mode of HZSM-5 and nK-CoFeOx, the synergistic effect of the two components promotes CO2 conversion and noteworthily increases the distribution of light-weight hydrocarbons, especially benzene, toluene, and xylene on composite catalyst by aromatization over active sites with appropriate acidity and proximity. This study provides valuable guidelines for designing selective and efficient iron-based composite catalysts to obtain value-added FTS products and light aromatics. Graphical Abstract: During CO2 hydrogenation, three types of active sites are thought to display cooperatively reinforced synergy: CO2 is first reduced to CO by RWGS on Fe3 O4 sites, and then CO is hydrogenated to low carbon hydrocarbons via FTS on Fe5 C2 sites. The low carbon hydrocarbons intermediates are produced on the iron-based sites and subsequently migrate to zeolite acid sites, where they conduct acid-catalyzed processes, resulting in the formation of gasoline-range isoparaffins and aromatics, which eventually diffuse out of zeolite pores. ga1 Highlights: Fe-Co interaction promotes the adsorption and dissociation of CO intermediates and carburization of iron species. The addition of K enhances CO2 adsorption and weakens H2 adsorption . The synergy of different active sites is crucialin the tandem catalysis process. Passivating zeolite acidity by Si treatment promotes the selectivity of liquid hydrocarbons. 5 K-CoFeOx(1:5)/HZSM-5 exhibits exceptional high liquid hydrocarbons space-time yield at 51.2% CO2 conversion.